2003
DOI: 10.1094/pdis.2003.87.2.159
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Broccoli Rotation on Lettuce Drop Caused by Sclerotinia minor and on the Population Density of Sclerotia in Soil

Abstract: Field experiments were conducted at Spence Road site and at the Hartnell College East Campus site in Salinas, CA, to determine the effects of crop rotation with broccoli or a fallow period on lettuce drop caused by Sclerotinia minor and the density of pathogen sclerotia in the soil. Treatments at the Spence Road site with low inoculum density (<7 sclerotia per 100 cm3 of soil) distributed randomly included: successive crops of lettuce (LLL), lettuce rotated with broccoli (LBL), and lettuce followed by a fal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(32 citation statements)
references
References 26 publications
0
32
0
Order By: Relevance
“…Incorporating cover crops can also produce bioactive compounds that behave similarly to chemical soil fumigants (biofumigation), causing changes in microbial communities and suppressing pests (Hao et al 2003;Koike and Subbarao 2000). In peaches, UC and USDA-ARS researchers found that short preplant rotations of sudangrass helped manage Prunus replant disease, improving calculated profits even when fruit prices were low .…”
Section: Cover Crops and Crop Rotationmentioning
confidence: 99%
“…Incorporating cover crops can also produce bioactive compounds that behave similarly to chemical soil fumigants (biofumigation), causing changes in microbial communities and suppressing pests (Hao et al 2003;Koike and Subbarao 2000). In peaches, UC and USDA-ARS researchers found that short preplant rotations of sudangrass helped manage Prunus replant disease, improving calculated profits even when fruit prices were low .…”
Section: Cover Crops and Crop Rotationmentioning
confidence: 99%
“…that produce glucosinalates, sudan grass and cereal rye (SAN 1998). Biofumigation with broccoli residue incorporation suppresses Sclerotinia minor in lettuce (Hao et al 2003) and Verticillium wilt in cauliflower when disease pressure is moderate. One reason for the variable performance of Brassica spp.…”
Section: Biotic Interactions In Agroecosystems C Shennan 725mentioning
confidence: 99%
“…But additional chemical compounds arising from nonglucosinolate pathways -including aldehydes, acids and other sulfur-and nitrogen-containing compounds released during plant growth or decomposition in soilalso have significant pesticidal activity (Kelly and Baker 1990;Gamliel and Stapleton 1993;Bending and Lincoln 1999). Furthermore, besides chemical activity, alterations in microbial activity (Gamliel and Stapleton 1993) that are deleterious to pest organisms (Hao et al 2003) have also been associated with Brassica-mediated soil disinfestation. In California, published results on biofumigation with Brassica spp.…”
Section: Biofumigation Of Soilsmentioning
confidence: 99%
“…Experimental work in the Salinas Valley reported that broccoli (B. oleracea var. italica) rotations were effective in controlling certain soilborne fungal pathogens, such as Verticillium and Sclerotinia, in vegetable crop rotations (Koike and Subbarao 2000;Hao et al 2003). In contrast, cropping and subsequent soil incorporation of rape/canola (B. napus) and certain mustards (B. juncea and Sinapis alba) had no significant effects on the soilborne pests of processing tomatoes in the Sacramento Valley (Hartz et al 2005).…”
Section: Biofumigation Of Soilsmentioning
confidence: 99%